Pembangunan Hukum Pidana : Pluralisme Hukum dalam RKUHP (Institut Pemerintahan Dalam Negeri, 2020)
The objective of this transcription is to elaborate informal law of criminal (law which living into society and natural law) which apparently acknowledge pluralism of law in system developmental of Indonesia’s law of criminal. The opportunity is which given by RKUHP to the judge for implementing informal law in the fact opposite whit legality principles and the interest create law assurance and non-discrimination prohibition. The another alternative which offered is adopting informal law norms into formal law of criminal, that is used whole citizen, the judge obligation is excavate, follow, and understand law values and justice sense which live in the society, it should be entered in yurisprudential developmental frame work.Keywords: Informal law of criminal, law assurance, yurisprudential.